Analysis of the Insulation Characteristics of Hexafluorobutene (C4H2F6) Gas and Mixture with CO2/N2 as an Alternative to SF6 for Medium-Voltage Applications - Ahmed, Rizwan; Abd Rahman, Rahisham; Adel S. Aldosary, Adel S. Aldosary; Baqer Al-Ramadan, Baqer Al-Ramadan; Ullah, Rahmat; Jamal, Arshad (Mdpi, 2023)
This paper investigates C4H2F6 , a promising environmentally friendly insulating gas that possesses high dielectric strength and a low global warming potential. The study focuses on examining the insulation properties of C4H2F6 when combined with CO2/N2 , aiming to assess its suitability as a substitute for SF6 in gas-insulated applications. Finite element analyses are performed to evaluate the field utilization factor and electric field distribution in the proposed mixture. The properties of liquefaction temperature were examined in this study to determine the optimal mixing ratio for applications that require a minimum working temperature. Extensive experimental investigations were carried out to assess the dielectric strength characteristics of the gas mixture in both uniform and quasi-uniform electric fields. It was found that pure HFO-1336mzz (E) exhibits a dielectric strength approximately 1.2–1.6 times higher than SF6 . Experimental results have revealed that the insulation performance of a 30% HFO-1336mzz (E)/CO2 mixture closely resembles that of SF6 , with a matching efficiency of up to 90% in a weakly uniform electric field. This remarkable performance can be attributed to a positive synergistic effect between HFO-1336mzz (E) and CO2 , combined with the gas mixture’s excellent self-recoverability property. These experimental findings are further supported by finite element analysis, which confirms the observed results. The 30% HFO-1336mzz (E)/CO2 gas mixture at 0.15–0.20 MPa pressure and constant 0.6 mm air gap reveal superior insulation tolerance and less sensitivity to the electric field, confirming its promising medium-voltage engineering applications. The associated results of this research provide a critical reference for the engineering application of the alternating (AC) and direct current (DC) insulation characteristics of the HFO-1336mzz (E)/CO2 gas mixture.